The effect of compensation, staffing status, and leadership style on employee performance through job satisfaction - Edi Sugiono; Haris Dharma Persada (JPPI (Jurnal Penelitian Pendidikan Indonesia))
The research phenomenon is that employee performance at the Secretariat of the General Election Supervisory Agency in DKI Jakarta Province has not been optimal. The purpose of the study was to determine the Effect of Compensation, Staffing Status, and Leadership Style on Employee Performance through Job Satisfaction as a Mediation Variable at the Secretariat of the General Election Supervisory Agency in DKI Jakarta Province. This research uses a quantitative approach with the PLS-SEM (Partial least square path modeling- structural equation modeling analysis) analysis method. Primary data collection techniques use questionnaire techniques. The study sample of 104 respondents using saturated models according to the minimum sample size was four times ten times the most significant structural number leading to the construct. Based on the discussion of the research results, it was concluded that the results were direct: there was a positive and significant influence of Compensation, Staffing Status, Leadership Style, and job satisfaction on Employee Performance at the Secretariat of the General Election Supervisory Agency in DKI Jakarta Province. Indirect results there is a positive and significant influence of compensation, staffing status, and leadership style on employee performance through job satisfaction as a mediation variable at the Secretariat of the General Election Supervisory Agency in DKI Jakarta Province.